Reasons And Real Selves - Manuel Vargas (Ideas y Valores)
Most accounts of responsibility begin from either of two prominent points of departure: the idea that an agent must have some characterological or expressive connection to the action, or alternately, the idea that an agent must be in some sense responsive to reasons. Here, I will argue that the relation between these two approaches to moral responsibility is much more complicated than is ordinarily assumed. I shall argue that there are reasons to think that one of these views may ultimately collapse into the other, and if not, that there is nevertheless reason to think one of these views has misidentified the features of agency relevant to moral responsibility. The view that follows is one that we might call the primacy of reasons. In the second half of the article I consider whether recent experimental work speaks in favor of the alternative to the primacy of reasons. Its proponents argue that it does. I argue that it does not.